Proceedings of the Creative Construction Conference 2019 2019
DOI: 10.3311/ccc2019-103
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing Applications in Construction from the Past and into the Future

Abstract: The advent of 3D printing technology may very well be remembered as one of the most important technological advances of the early twenty-first century. This technology is transforming the dynamics of the manufacturing world in ways that may have not been thought possible a couple of decades ago. 3D printing is now being used in medicine and dentistry to make prosthetic parts, sensors, and medical models among a number of other applications. The versatility of the types of materials that can be 3D printed makes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…DLP creates 3D models that are more robust and have a higher resolution. It also requires less material, which reduces expenses and waste (Alzarrad and Elhouar, 2019). For constructing a single layer of a 3D object by spatially controlled solidification using a projector light, the digital light processing (DLP) technology employing photocurable resins is fascinating (either UV or white light).…”
Section: Awareness Of 3d Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…DLP creates 3D models that are more robust and have a higher resolution. It also requires less material, which reduces expenses and waste (Alzarrad and Elhouar, 2019). For constructing a single layer of a 3D object by spatially controlled solidification using a projector light, the digital light processing (DLP) technology employing photocurable resins is fascinating (either UV or white light).…”
Section: Awareness Of 3d Technologiesmentioning
confidence: 99%
“…As technology has progressed, 3D printing has expanded to accommodate construction products other than ceramic in recent years. In construction projects, 3D printers can currently produce plastic and nylon components such as plug fixtures, window frame fixtures, and plumbing fittings (Alzarrad and Elhouar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The research methods for the 3D printing construction studies were analysed, and the results showed that around 32% of the publications are review articles that were performed in a systematic way. Scholars use this method to synthesise and interpret past research [73] to present the organised history of a specific topic [56] and to deliver new ideas for current conditions. For example, by overviewing recent attempts at applying 3D printing technology, Alzarrad and Elhouar [56] elucidated the sector's successes and challenges.…”
Section: Interpretation Of Research Methods For 3d Printing Construct...mentioning
confidence: 99%
“…The benefits and challenges in the 3D printing sector are a continuing research topic. The benefits and challenges of 3D printing adoption have been widely investigated [15,[55][56][57]. This provides a sufficient background study for future research on the topic of 3D printing.…”
Section: Interpretation Of Existing Research Focusesmentioning
confidence: 99%
“…AI could help robots to perform repetitive tasks more efficiently than their human counterparts, such as pouring concrete, bricklaying, welding, and demolition, etc. [25]. This releases up human workers for other construction activities and reduces the overall time required to complete the project.…”
Section: Ai In Construction Managementmentioning
confidence: 99%